Effect of tantalum contents on transformation temperatures, thermal behaviors and microstructure of CuAlTa HTSMAs - Ercan, E.; Dagdelen, F.; Qader, I. N. (Springer, 2020)
In this study, CuAl13-xTax (% mass x = 1; 1.5; 2; 2.5) shape-memory alloys were produced through arc-melting method. Phase transformation temperatures were investigated by using differential scanning calorimetry (DSC) and thermogravimetric analysis. Microstructures were examined with the aid of optical microscopy, scanning electron microscopy-energy-dispersive X-ray (SEM-EDX) and X-ray diffraction (XRD). The ratios of electron per atom (e/a) for CuAl13-xTa1, CuAl13-xTa1.5, CuAl13-xTa2 and CuAl13-xTa2.5 were calculated as 1.52, 1.51, 1.50 and 1.49, respectively. DSC results showed that CuAlTa alloys belong to high-temperature shape-memory alloys. Also, it was identified that these alloys demonstrate 2H(gamma 1 ')-> DO3(beta 1)-> 18R(beta 1 ') phase transformation. It was observed that both phase transformation temperature and oxidation sensitivity of the samples decreased with the increase in the amount of Ta. In the XRD analysis of CuAlTa HTSMA alloys, some phases were observed, including gamma ',beta ' Cu9Al4, CuAl and Ta2Al3. These phases were supported by SEM-EDX results. The micro-hardness values of the alloys were increased by increasing Ta content.
2nd Journal of Thermal Analysis and Calorimetry Conference (JTACC) / 7th Joint Czech-Hungarian-Polish-Slovakian Thermoanalytical Conference (V4) -- JUN 18-21, 2019 -- Budapest, HUNGARY
Keywords: Martensitic phase; Microstructure; Oxidation sensitivity; Shape-memory alloy